1993
DOI: 10.1007/bf01006894
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of interactions of 5?-derivatives of deoxyoctathymidylate with human DNA polymerize ? and HIV reverse transcriptase

Abstract: Km and Vmax values for d(pT8) and its derivatives containing various 5'-end groups were estimated in the reaction of DNA polymerization alpha catalyzed by DNA polymerase alpha and HIV-RT. The effect of 5'-end modification of primer is more pronounced in the case of HIV-RT. Strong influence is observed for an intercalating (ethidium) group. The affinity of EtpT8 is 200-fold higher than that of d(pT8). Attachment of Phn-, Dnm- and Hem-groups results in the increase of affinity of modified primer from 10 up to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Because such compounds significantly increased the stability of complexes formed by complementary ODNs in solution (Balbi et al, 1994(Balbi et al, , 1997, it was reasonable to suppose that the observed increase in primer affinity was due to the intercalating properties of these compounds. Although we have already shown that the ethidium group had an important effect on the interaction between RT and primer (Khodyreva et al, 1993), its influence was markedly lower than that produced by the two new modifying groups.…”
Section: Inhibition Of Rt By Odn Derivativesmentioning
confidence: 65%
See 2 more Smart Citations
“…Because such compounds significantly increased the stability of complexes formed by complementary ODNs in solution (Balbi et al, 1994(Balbi et al, , 1997, it was reasonable to suppose that the observed increase in primer affinity was due to the intercalating properties of these compounds. Although we have already shown that the ethidium group had an important effect on the interaction between RT and primer (Khodyreva et al, 1993), its influence was markedly lower than that produced by the two new modifying groups.…”
Section: Inhibition Of Rt By Odn Derivativesmentioning
confidence: 65%
“…At the same time, it should be noted that the features of DNA interaction with some compounds in solution cannot always be extrapolated to the interaction of nucleic acids in complexes with enzymes, because the latter cause substantial structural changes in the nucleic acid regions situated within the protein globule (for review, see Nevinsky, 1995). For example, ODNs containing the 5'terminal phenazine group demonstrated a comparable affinity for complementary DNA and RNA in solution, while the affinity of the derivative of d(pT)8 was about two orders of magnitude higher for poly(A) than that for poly(dA) template in their complexes with HIV-1 RT (Khodyreva et al, 1993). Such changes in the interaction seem to result from alterations in nucleic acid structure after binding to the enzyme.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the interaction of nucleic acid with different compounds including MGBs, there may be significant differences depending on whether they are free or complexed with enzymes (38–40). For example, oligonucleotides containing the phenazinium group at the 5′‐end showed a similar affinity for the complementary DNA or RNA in solution, while the affinity of these derivatives for the nucleic acids was about two orders of magnitude higher in their complexes with HIV‐1 RT (41). Thiazole containing polyamides demonstrated significantly higher affinity to RNA·DNA complexes with HIV‐1 RT than to the same RNA·DNA duplexes in solution (30).…”
Section: Resultsmentioning
confidence: 99%